2000
DOI: 10.1016/s0029-7844(00)01051-6
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous mastitis in pregnancy

Abstract: Granulomatous mastitis is diagnosed clinically and histologically. Early recognition and initiation of steroid treatment might prevent repetitive, deforming breast biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 7 publications
1
42
0
Order By: Relevance
“…Evidence in the literature has shown that most patients with granulomatous mastitis have a troublesome course of recurrence and unfortunately the original treatment of multiple surgical intervention has been associated with increased rates of wound infection, sinus formation and poor cosmesis 6,7 , 9 . Over the last 20 years the use of prednisone alone in high doses has been shown to have a good response 15−18 and this fits in with the autoimmune aetiology hypothesis, but there has been a tendency for side‐effects and we have found that relapses can occur when reduced to the lower doses. We have found that the use of methotrexate in conjunction with prednisone is excellent in that it enabled 100% of patients in the present series to come off prednisone without relapse and then stay in remission.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Evidence in the literature has shown that most patients with granulomatous mastitis have a troublesome course of recurrence and unfortunately the original treatment of multiple surgical intervention has been associated with increased rates of wound infection, sinus formation and poor cosmesis 6,7 , 9 . Over the last 20 years the use of prednisone alone in high doses has been shown to have a good response 15−18 and this fits in with the autoimmune aetiology hypothesis, but there has been a tendency for side‐effects and we have found that relapses can occur when reduced to the lower doses. We have found that the use of methotrexate in conjunction with prednisone is excellent in that it enabled 100% of patients in the present series to come off prednisone without relapse and then stay in remission.…”
Section: Discussionsupporting
confidence: 70%
“…Usually no further therapy is required thereafter but recurrence and delayed wound healing can occur relatively commonly. More recently, the use of corticosteroids has been shown to be effective, especially in refractory or recurrent cases 15−18 . However, corticosteroids do have major side‐effects, the efficacy has been shown to be variable and recurrences have occurred when the steroids have been withdrawn.…”
Section: Introductionmentioning
confidence: 99%
“…Before diagnosing IGM, any known cause of granulomatous breast inflammation, such as duct ectasia, sarcoidosis, Wegener's granulomatosis, giant cell arteritis, polyarteritis nodosa, tuberculosis, syphilis, corynebacterial infection, cat-scratch disease in breast lymph node tissue, mycotic infection, granulomatous reaction in a carcinoma and foreign body reaction, whether infectious or non-infectious, should be ruled out [5-7]. Duct ectasia can mimic IGM as both possess similar clinical symptoms, including nipple retraction, pain, and occasional bloody discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The disease usually occurs around 2 years after breastfeeding at a median age of 30 years [6]. Only 2 reports of male GM [7,8] and a few reports of women developing GM during pregnancy or lactation exist [9,10]. …”
Section: Prevalence and Etiologymentioning
confidence: 99%